Supplementary dataset Pinus Taeda [Conjunto de datos] - Cappa, Eduardo Pablo (2020)
Trial information and family numbers of the Pinus Taeda L. trial. Diameter at breast height of the Pinus taeda L. data set will be available upon request. Supplementary dataset Pinus Taeda for Cappa, E.P., Muñoz, F., Sanchez, L. et al. A novel individual-tree mixed model to account for competition and environmental heterogeneity: a Bayesian approach. Tree Genetics & Genomes 11, 120 (2015).